2021
DOI: 10.3390/insects12020115
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Double-Stranded Ribonuclease Improves Oral RNAi Efficacy in Southern Green Stinkbug Nezara viridula

Abstract: Variability in RNA-interference (RNAi) efficacy among different insect orders poses a big hurdle in the development of RNAi-based pest control strategies. The activity of double-stranded ribonucleases (dsRNases) in the digestive canal of insects can be one of the critical factors affecting oral RNAi efficacy. Here, the involvement of these dsRNases in the southern green stinkbug Nezaraviridula was investigated. First, the full sequence of the only dsRNase (NvdsRNase) in the transcriptome of N. viridula was obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 61 publications
(50 reference statements)
3
19
0
2
Order By: Relevance
“…The protection of dsRNA from nuclease will be a better way of achieving optimum knockdown in C. partellus and facilitating RNAi-mediated control strategy. Efforts to protect dsRNA from nucleases degradation by silencing nuclease have been demonstrated to enhance dsRNA uptake in agricultural pests and subsequently improve RNAi efficiency (Giesbrecht et al 2020;Wang et al 2020;Sharma et al 2021). Research evidence has shown that nanoparticle-mediated delivery overcomes poor cellular internalization and nucleolytic degradation of dsRNAs for effective RNAi response in insect cells (Christiaens et al 2018;Dhandapani et al 2019;Wang et al 2019;Baddar et al 2020;Yan et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The protection of dsRNA from nuclease will be a better way of achieving optimum knockdown in C. partellus and facilitating RNAi-mediated control strategy. Efforts to protect dsRNA from nucleases degradation by silencing nuclease have been demonstrated to enhance dsRNA uptake in agricultural pests and subsequently improve RNAi efficiency (Giesbrecht et al 2020;Wang et al 2020;Sharma et al 2021). Research evidence has shown that nanoparticle-mediated delivery overcomes poor cellular internalization and nucleolytic degradation of dsRNAs for effective RNAi response in insect cells (Christiaens et al 2018;Dhandapani et al 2019;Wang et al 2019;Baddar et al 2020;Yan et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A double‐stranded RNA nuclease was associated with rapid degradation of dsRNA in the saliva of the southern green stinkbug ( Nezara viridula ). And the blockage of dsRNA nuclease synthesis significantly enhances the RNAi efficacy via orally delivered dsRNA in N. viridula (Sharma et al ., 2021). To overcome this barrier, formulation of dsRNA with polymer or liposomic nanoparticles was a strategy, which can prevent degradation of dsRNA in the digestive system of insects (Christiaens et al ., 2018; 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Given these challenges, a recent breakthrough was achieved, demonstrating that chitosan nanoparticles-mediated dsRNA delivery in Helicoverpa armigera protects from degradation by nucleases and insect gut pH (Kolge et al, 2021). Beyond shielding dsRNA from RNase degradation, the silencing of a dsRNA ribonuclease improved oral RNAi efficacy in the southern green stinkbug (Sharma et al, 2021). This finding indicates that the simultaneous application of protective agents such as RNase inhibitors or the silencing of dsRNases might encourage targeted detoxification mediated by P450s, ABC transporters and others (Wang et al, 2021).…”
Section: Significant Advances Of Rna Spray Controlling: Insectsmentioning
confidence: 99%